Polypills for Primary Prevention of Cardiovascular Disease: A Systematic Review and Meta-Analysis - Kandil, Omneya A.; Motawea, Karam R.; Aboelenein, Merna M.; Shah, Jaffer (Frontiers in Cardiovascular Medicine, 2022)
Purpose To evaluate the effect of polypills on the primary prevention of cardiovascular (CV) events using data from clinical trials. Methods We searched PubMed, Web of Science, EBSCO, and SCOPUS throughout May 2021. Two authors independently screened articles for the fulfillment of inclusion criteria. The RevMan software (version 5.4) was used to calculate the pooled risk ratios (RRs) and mean differences (MDs), along with their associated confidence intervals (95% CI). Results Eight trials with a total of 20653 patients were included. There was a significant reduction in the total number of fatal and non-fatal CV events among the polypill group [RR (95% CI) = 0.71 (0.63, 0.80); P-value < 0.001]. This reduction was observed in both the intermediate-risk [RR (95% CI) = 0.76 (0.65, 0.89); P-value < 0.001] and high-risk [RR (95% CI) = 0.63 (0.52, 0.76); P-value < 0.001] groups of patients. Subgroup analysis was performed based on the follow-up duration of each study, and benefits were only evident in the five-year follow-up duration group [RR (95% CI) = 0.70 (0.62, 0.79); P-value < 0.001]. Benefits were absent in the one-year-or-less interval group [RR (95% CI) = 0.77 (0.47, 1.29); P-value = 0.330]. Additionally, there was a significant reduction in the 10-year predicted cardiovascular risk in the polypill group [MD (95% CI) = −3.74 (−5.96, −1.51); P-value < 0.001], as compared to controls. Conclusion A polypill regimen decreases the incidence of fatal and non-fatal CV events in patients with intermediate- and high- cardiovascular risk, and therefore may be an effective treatment for these patients.